(untitled) (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2023)
Pangkajene dan Kepulauan regency are one of the blue swimming crabs fishing center and processing located in South Sulawesi. This research is conducted to analyze the biological aspect and the usage status of blue swimming crab (Portunus pelagicus) on the coast of Pangkajene dan Kepulauan regency. Data collection used a survey method by conducting interviews with fishermen, observing research sites and measuring crabs directly in the field. Samplings were obtained twice a month from November 2018 to April 2019. 7200 Portunus crabs from the fisherman were randomly selected to measure the size and the weight which consists of 3900 male and 3300 female crabs from different districts were Pangkajene, Bungoro, Labakkang, Ma’rang, Segeri, and Mandalle. The measurement result are then analyzed using Microsoft Excel program and ELEFAN I method in FISAT II program. The result showed that the maximum age of blue swimming crab predicted can reach 4 years, with the natural mortality (M) of Portunus male crabs is 0.67 and female crabs 0.82 per year then fishing mortality (F) is 3.54 and 4.12 per year. The total mortality (Z) is 4.20 and 4.94 per year with the exploitation rate (E) around 0.84 and 0.83. Therefore, based on the system dynamics model of non-equilibrium fish biomass resulted that the biology status of blue swimming crabs on Pangkep regency has reached the overfishing condition.